Antitumor T cell responses in bladder cancer are directed against a limited set of antigens and are modulated by regulatory T cells and routine treatment approaches. Issue 9 (11th July 2013) - Horn, Thomas; Grab, Jessica; Schusdziarra, Julia; Schmid, Sebastian; Maurer, Tobias; Nawroth, Roman; Wolf, Petra; Pritsch, Maria; Gschwend, Jürgen E.; Kübler, Hubert R.; Beckhove, Philipp
<x xml:space="preserve">Abstract</x> Regulatory T cells (Tregs) play a key role in cancer immune escape. We identified target antigens of spontaneous tumor‐specific T cell responses in urothelial carcinoma (UC) and evaluated their modulation by treatment and Treg. We determined Treg target antigens in UC. Fifty‐six UC and 13 control patients were prospectively enrolled. Blood was drawn before and after routine treatment. Changes in Treg frequency were measured by fluorescence cytometry and the T effector cell (Teff) response against a set of nine tumor‐associated antigens (TAAs) was monitored with an interferon‐gamma ELISpot. Antigen specificity of Treg was determined by their increased capacity to inhibit after TAA‐specific activation the proliferation of an autologous T cell population. The highest difference in the overall response rate for the total T cell population was observed for epidermal growth factor receptor (EGFR) (UC: 23% and controls: 0%). After depleting Treg, also new york esophageal (NYES)O1 (19 and 0%) and MUC20 (27 and 0%) were more frequently recognized in UC patients. In metastasized patients, the TAA‐directed T cell response was augmented by Treg depletion. Tumor resection seemed to diminish Treg suppression of TAA‐specific immunity, whereas chemotherapy had no effect. We demonstrated the existence of TAA‐specific Treg in UC, which share antigen specificities with Teff. The coexistence of TAA‐specific Treg and Teff was very rare. Treg frequencies in the peripheral blood were not changed by therapy. In summary, we identified potentially immunologically relevant TAA in UC. TAA‐specific T cell responses against these antigens are suppressed by Treg. We identified TAA‐specific Treg in UC patients, which do not cooccur with TAA‐specific Teff.